Higher self-control predicts engagement in undesirable moralistic aggression - Rai, Tage S. (Personality and individual differences, 2019)
Lack of self-control is considered to be a key factor in generating aggression and violence. However, across two studies, aggression was associated with greater self-control when participants felt that violence was undesirable but morally required. Using a within-subjects retrospective method, in Study 1 (N = 95) participants recalled having greater self-control when they themselves engaged in aggression as a perpetrator that they felt was automatically aversive but morally right compared to when they avoided such aggression. The opposite pattern was found for aggression that participants felt was automatically desirable but morally wrong, replicating prior results. Using a between-subjects vignette-based method, in Study 2 (N = 213), it was found that higher trait levels of self-control predicted greater willingness to fight when participants saw aggression as undesirable but morally right in a hypothetical scenario. Implications of these findings are discussed in terms of how perpetrator motivation determines the role of self-control in aggression. •Participants recall having more self-control during undesirable, moral aggression.•Participants recall having less self-control during desirable, immoral aggression.•High trait self-control predicts greater support for undesirable, moral aggression.